Patient‐specific independent 3D GammaPlan quality assurance for Gamma Knife Perfexion radiosurgery. (7th January 2013) - Mamalui‐Hunter, Maria; Yaddanapudi, Sridhar; Zhao, Tianyu; Mutic, Sasa; Low, Daniel A.; Drzymala, Robert E.
Abstract : One of the most important aspects of quality assurance (QA) in radiation therapy is redundancy of patient treatment dose calculation. This work is focused on the patient‐specific time and 3D dose treatment plan verification for stereotactic radiosurgery using Leksell Gamma Knife Perfexion (LGK PFX). The virtual model of LGK PFX was developed in MATLAB, based on the physical dimensions provided by the manufacturer. The ring‐specific linear attenuation coefficients (LAC) and output factors (OFs) reported by the manufacturer were replaced by the measurement‐based collimator size‐specific OFs and a single LAC = 0.0065   mm − 1 . Calculation depths for each LGK PFX shot were obtained by ray‐tracing technique, and the dose calculation formalism was similar to the one used by GammaPlan treatment planning software versions 8 and 9. The architecture of the QA process was based on the in‐house online database search of the LGK PFX database search for plan‐specific information. A series of QA phantom plans was examined to verify geometric and dosimetric accuracy of the software. The accuracy of the QA process was further evaluated through evaluation of a series of patient plans. The shot time/focus point dose verification for each shot took less than 1 sec/shot with full 3D isodose verification taking about 30 sec/shot on a desktop PC. GammaPlan database access time took less than 0.05 sec. The geometric accuracy (location of the point of maximum dose) of the phantom and patient plan was dependent on the resolution of the original dose matrix and was of the order of 1 dose element. Dosimetric accuracy of the independently calculated phantom and patient point (focus) doses was within 3.5% from the GammaPlan, with the mean = 2.3 % and SD = 1.1 % . The process for independent pretreatment patient‐specific Gamma Knife Perfexion time and dose verification was created and validated. PACS numbers: 87.53.Bn; 87.55.‐x; 87.56.Bg